Does manager turnover improve firm performance? New evidence using information from Dutch soccer, 1986 - 2004 - Bas ter Weel (Institute for the Study of Labor (IZA), 2006)
This research examines the impact of manager turnover on firm performance using information from the Dutch soccer league in the period 1986-2004. The advantage of using sports data is that both manager characteristics and decisions and firm outcomes are directly observable. Both difference-in-difference and 2SLS estimates suggest no improvements in firm performance after manager turnover, whereas previous research based on publicly traded firm data has found positive but very small effects of manager turnover on firm performance. In addition, manager quality does not seem to matter in predicting turnover. These estimates are compared and contrasted with studies using publicly traded firm data.
urn:nbn:de:101:1-2008051364
Keywords: 330